The study of fire safety status and awareness among workers at Utilities Gebeng - Roslan, Wan Hazwani Wan Mohammad (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2014)
The general objective of this research is to determine the fire safety status and fire safety awareness among workers at Utilities Gebeng (UG). The specific objectives are to compare the fire safety knowledge, attitude, and practice (KAP) fire safety level among workers at UG; to compare the fire safety status of three buildings at UG; to determine the relationship between fire safety status and fire safety awareness of workers and find the difference of fire safety awareness based on gender and education level. 109 respondents were involved in this research. Checklist was used to determine fire safety status. Meanwhile, questionnaire was used to determine fire safety awareness. Checklist consisted of workplace regulation and management regulation while questionnaire consisted of 34 questions with two sections. Data were also collected by document review on several records of UG. From the findings, administration building and Main Control Building (MCB) obtained 33 scores while Maintenance building achieved 32 scores for fire safety status. The score on questionnaires showed the majority of respondents had high score (knowledge= 76.15%, attitude= 54.13%, practice= 77.98%). This is because the company had practice good fire safety system. There was a significant difference of fire safety awareness level on knowledge (p=0.001), attitude (p=0.002), and practice (p=0.001) between permanent and contract workers. There was no significant association between fire safety status and fire safety awareness. There was a significant difference of fire safety between awareness males and females workers (p=0.017) and education level (p=0.001). Although the fire safety status and fire safety awareness level at UG were high, several measures were recommended to prevent fire incidents from occurring in the future.